Effects of proxeed plus in the prevention and treatment of cisplatin nephrotoxicity: An experimental rat study - Doğan, Elif Ece; Aydın, Mehmet Şerif; Güler, Eray Metin; Koçyiğit, Abdurrahim; Gürsu, Meltem; Şeker, Mesut; Kazancıoğlu, Rümeyza (Oxford University Press, 2018)
[Abstract Not Available]
55th Congress of the European-Renal-Association (ERA) and European-Dialysis-and-Transplantation-Association (EDTA) -- MAY 24-27, 2018 -- Copenhagen, DENMARK
WOS: 000433059801179
Keywords: Proxeed Plus; Prevention; Treatment; Cisplatin Nephrotoxicity